Prevalence of Gardnerella vaginalis in cervical Papanicolaou smears of patients attended at a pathology laboratory in Bento Gonçalves, RS - Dallacort, Daiane; Dalzochio, Thaís (REVISTA CEREUS, 2022)
This study aimed to verify the prevalence of Gardnerella vaginalis in cervical Papanicolaou smears of patients attended at a pathology laboratory in the city of Bento Gonçalves, RS. A retrospective cross-sectional and descriptive study was performed by analyzing 49617 cytopathological reports issued from January 1, 2016 to December 31, 2020. A total of 21.86% (10.839/49617) positive reports for G. vaginalis were found, and the years 2020 and 2017 presented the highest and lowest prevalences, corresponding to 25.28% and 19.40%, respectively. The mean age of patients was 45.59 years, and the highest prevalence was found in patients aged 51 to 60 years corresponding to 22.74%. The fungus Candida sp. was observed in 3.60% of the reports positive for G. vaginalis. Among the cytopathological alterations associated with G. vaginalis, the atypical cells of undetermined significance (ASC-US) result was the most predominant, in 3.97% of the reports. Therefore, the results obtained showed a considerable prevalence of the bacteria in pap smears reports. Thus, it is necessary to inform the female population about the diagnosis and treatment of the bacteria, to avoid possible complications.